2005
DOI: 10.1093/ejo/cji102
|View full text |Cite
|
Sign up to set email alerts
|

Galvanic corrosion between orthodontic wires and brackets in fluoride mouthwashes

Abstract: The aim of this investigation was to determine the influence of fluoride in certain mouthwashes on the risk of corrosion through galvanic coupling of orthodontic wires and brackets. Two titanium alloy wires, nickel-titanium (NiTi) and copper-nickel-titanium (CuNiTi), and the three most commonly used brackets, titanium (Ti), iron-chromium-nickel (FeCrNi) and cobalt-chromium (CoCr), were tested in a reference solution of Fusayama-Meyer artificial saliva and in two commercially available fluoride (250 ppm) mouthw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 29 publications
2
62
2
2
Order By: Relevance
“…This is considered a consequence of the release of the trace amounts of silver and copper present in some commonly used solutions, tubes, bottles, bottle caps, and clips. Although there are several studies that have investigated corrosion on orthodontic appliances caused by mouthwashes, 19,[28][29][30] there are not many studies that have investigated the effects of mouthwashes on different soldering applications. Our finding is that the greatest amount of metal ion release occurs in NaF + alcohol containing mouthwashes and may contribute to both the literature and to clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is considered a consequence of the release of the trace amounts of silver and copper present in some commonly used solutions, tubes, bottles, bottle caps, and clips. Although there are several studies that have investigated corrosion on orthodontic appliances caused by mouthwashes, 19,[28][29][30] there are not many studies that have investigated the effects of mouthwashes on different soldering applications. Our finding is that the greatest amount of metal ion release occurs in NaF + alcohol containing mouthwashes and may contribute to both the literature and to clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 It has been reported that mouthwashes increase the risk of corrosion and cause the release of some metals from the surface of orthodontic appliances. [27][28][29][30] There are no prior studies in the literature that investigate the relationships between various mouthwashes, metal ion release, and various soldering methods. The aim of the present study was to compare the release of nickel, chromium, iron, silver, and copper ions; the corrosion rate; and the amount of corrosion for two different soldering methods used in the preparation of orthodontic appliances-laser welding and silver soldering-in three different mouthwash solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies 10,11 have shown that a NiTi orthodontic archwire in commercially available fluoride mouthwashes (fluoride ion: close to 250 ppm) can corrode. In this study, the corrosion resistance, in terms of R p , of the test NiTi archwires decreased as the NaF concentration increased (Table 2), regardless of archwire manufacturer.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] Since the outermost surface of NiTi archwire contains mainly TiO 2 film with small amounts of NiO, 9 fluorideenhanced corrosion of the NiTi archwire may occur. The corrosion behavior of a NiTi archwire in fluoride-containing mouthwashes (fluoride ion: a few hundred parts per million) 10,11 or prophylactic gels (fluoride ion: close to or more than 10,000 ppm) 12 has been investigated. However, information on the influence of fluoride concentration, contained in commercial fluorinated toothpastes (fluoride ion: a few hundred to a few thousand parts per million), on the corrosion resistance of commercial NiTi orthodontic archwires is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…This has implications not only in the development of contact sensitivity reac tions but also in decreased mechanical properties of the wire. 17 The amount of corrosion from differ ent alloys, however, has not been clini cally demonstrated. Factors including intra-oral temperature, pH, salivary composition, duration of exposure, wear of the wire due to friction from sliding mechanics, abrasion, presence of solder, strain of the wire and most importantly the amount of nickel that is leached are factors determining the concentration of nickel present from a particular appliance.…”
Section: Epidemiologymentioning
confidence: 99%